2022
DOI: 10.2147/ijwh.s361964
|View full text |Cite
|
Sign up to set email alerts
|

Premenstrual Syndrome and Its Association with Perceived Stress: The Experience of Medical Students in Jordan

Abstract: Objective To assess the prevalence of premenstrual and menstrual symptoms and to investigate premenstrual severity’s association with perceived stress of premenstrual syndrome among medical students. Methods This is a cross-sectional study. Data were collected between March and April 2021, a self-administered online questionnaire ( Supplementary Material ) was distributed to a sample of female medical students in Jordan (n=594). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…The result of the study showed that the prevalence of primary dysmenorrhea was high (82.6%) among female high school students in Yangon Adventist. The prevalence of dysmenorrhea was higher than the study carried out among Jordan medical students 75.4%, 14 Chinese university students 41.7%, 8 Gondar university students 77.6%, 9 Ghana adolescents 68.1%, 15 Palembang high school students 67.5%. 16 On the other hand, the prevalence of dysmenorrhea was lower than in the study conducted among Turkey university students 90.1%, 17 Swedish adolescents 89%, 7 Kuwait high-school students 85.6%, 18 Indian college girls 84.2%, 19 northern Ghana university students 83.6%.…”
Section: Discussionmentioning
confidence: 54%
“…The result of the study showed that the prevalence of primary dysmenorrhea was high (82.6%) among female high school students in Yangon Adventist. The prevalence of dysmenorrhea was higher than the study carried out among Jordan medical students 75.4%, 14 Chinese university students 41.7%, 8 Gondar university students 77.6%, 9 Ghana adolescents 68.1%, 15 Palembang high school students 67.5%. 16 On the other hand, the prevalence of dysmenorrhea was lower than in the study conducted among Turkey university students 90.1%, 17 Swedish adolescents 89%, 7 Kuwait high-school students 85.6%, 18 Indian college girls 84.2%, 19 northern Ghana university students 83.6%.…”
Section: Discussionmentioning
confidence: 54%
“…However, a study found that 49.4% of students do nothing, this figure is a bit higher compared to the current study findings where 30.6% of students did nothing. The female students' academic performance and university related duties might be undesirably affected by PMS [24].…”
Section: Discussionmentioning
confidence: 99%
“…The current findings revealed that backpain, breast tenderness, abdominal bloating, acne, restlessness, anxiety, and irritability were the most common symptoms reported to be experienced by the students. Similarly, in a study conducted in Jordan on 594 medical students, it was found that the majority of students experienced breast tenderness, bloating, nervousness, anxiety and mood swings to a moderate level [24]. Likewise, other studies found that breast tenderness, abdominal bloating and headache were the most common symptoms reported by students [25,26].…”
mentioning
confidence: 88%
“…Several estrogen receptors (ER) have been found in skeletal muscle, including the membrane-bound GPER and nuclear-type ER-α/β, both of which are activated upon binding with estrogen molecules [1][2][3][4][5]. During or before menstruation, when blood estrogen levels decrease, many women frequently experience increased fatigue and diminished energy levels [6,7]. Additionally, estrogen deficiency, often seen in menopausal women, has been linked to a range of musculoskeletal and neuromuscular disorders, such as sarcopenia, 2 of 16 osteoporosis, frailty, obesity, dementia, atherosclerosis, metabolic syndrome, and type 2 diabetes, with reported benefits when endogenous estrogen levels rise or exogenous estrogen is supplemented [2,[8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%